2014
DOI: 10.1111/jai.12498
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal occurrence and feeding habits of tonguefish,Cynoglossus lightiNorman, 1925, larvae in Ariake Bay, Japan

Abstract: Summary Spatiotemporal occurrence and feeding habits of tonguefish (Cynoglossus lighti Norman, 1925) larvae were investigated in an offshore area (>5 m in depth) of the inner part of Ariake Bay, Japan. All specimens were symmetric, free‐swimming larvae. Although their seasonal abundance and distribution in the study site varied from year to year, spawning started in June and the larval abundance was high in August and September with a wide distribution in the inner part of the bay. Both present and previous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Copepod nauplii and eggs were mainly eaten by the preflexion stages of these families, and it is noted that the ingested copepod eggs could also be contributed by the detached eggs of egg-bearing copepods. Our findings are consistent with the study by Kume et al (2015) in Japanese waters for the diet of Cynoglossus lighti which prey mainly on paracalanid (P. crassirostris), harpacticoid (M. norvegica) and oithonid (Oithona davisae) copepods. Sampey et al (2007) reported a similar dietary composition of harpacticoids, cyclopoids and calanoids for the postflexion stages of the Cynoglossidae and Callionymidae in Australian waters.…”
Section: Key Prey Species Of Tropical Larval Fishessupporting
confidence: 92%
“…Copepod nauplii and eggs were mainly eaten by the preflexion stages of these families, and it is noted that the ingested copepod eggs could also be contributed by the detached eggs of egg-bearing copepods. Our findings are consistent with the study by Kume et al (2015) in Japanese waters for the diet of Cynoglossus lighti which prey mainly on paracalanid (P. crassirostris), harpacticoid (M. norvegica) and oithonid (Oithona davisae) copepods. Sampey et al (2007) reported a similar dietary composition of harpacticoids, cyclopoids and calanoids for the postflexion stages of the Cynoglossidae and Callionymidae in Australian waters.…”
Section: Key Prey Species Of Tropical Larval Fishessupporting
confidence: 92%
“…Consequently, reliability of conclusions of these earlier studies is difficult to assess. Although several previous investigations concluded that C. lighti is a synonym of C. joyneri (Matsubara 1955;Menon 1977;Wang et al 2018), C. lighti still appears in contemporary literature (Koshiishi et al 2001;Yamaguchi & Kume 2004;Yagi et al 2009;Kume et al 2012;Ping & Liu 2014;Kume et al 2015;Song et al 2015;Wang et al 2018;Sun et al 2021) indicating that taxonomic status of these nominal species remains unresolved.…”
Section: Introductionmentioning
confidence: 99%